Comparative study of manual uterine displacement and wedge under right hip in prevention of supine hypotension syndrome in caesarean section under spinal anesthesia - Babu Gonuguntla, Srihari; Jampala, Sandhya (International Journal of Medical Research and Review, 2016)
Introduction: Supine hypotension syndrome results in signs of shock, by decrease in maternal blood pressure. This may result in life threatening complications in mother and fetus. To reduce the incidence of supine hypotension syndrome, few practices were recommended by authors in maternal positioning during C-section. Here in this study we are comparing hemodynamic stability between manual uterine displacement and wedge under right hip. Materials and Methods: 30 parturients were studied by left ward Manual Uterine Displacement (MUD), assigned as Group MUD. Another 30 parturients were studied by placing a 12 cm wedge under right hip (which gives 150 left lateral tilt), assigned as Group Wedge. Hemodynamic stability was assessed in between MUD and Wedge groups. Results: Systolic blood pressure was lower with wedge under right buttock or hip than Manual Uterine Displacement and it is statistically insignificant. Diastolic Blood pressure fall was almost similar in both the groups. There is a gradual fall in Mean Arterial Pressure in both groups, which is not significant. Heart rate was lower in Wedge Group when compared to MUD group but it was statistically insignificant. Conclusion: There is no much difference in Hemodynamic changes either by Manual uterine displacement or Wedge under right hip. Surgeons and patients feel more comfortable with Manual uterine displacement than Wedge under right hip, but anesthetists feel better with wedge because there is no need to hold the uterus continuously till delivery of the baby, so anesthesiologist can engage in patient monitoring and treatment.